Vegetation changes and plant wax biomarkers from an ombrotrophic bog define hydroclimate trends and human-environment interactions during the Holocene in Northern Norway - Balascio, Nicholas L.; Anderson, R. Scott; D’Andrea, William J.; Wickler, Stephen; D’Andrea, Robert; Bakke, Jostein (The Holocene, 2020)
Holocene climate records from northern Europe improve our understanding of important North Atlantic ocean and atmospheric circulation systems to long-term insolation-driven changes, as well as more rapid forcing and feedback mechanisms. Here we assess Holocene climate and environmental changes in northern Norway based on the analysis of pollen, non-pollen palynomorphs, plant macrofossils, and plant wax biomarkers from a high latitude ombrotrophic bog. We define the extent and thickness of Hollabåttjønnen Bog (0.16 km 2 ), which is located 10 km north of Tromsø. Several cores were analyzed, including a 5.16-m core that spans the last 9.5 cal ka BP. Vegetation changes from several sites were reconstructed and the distribution and hydrogen isotopic composition (δD) of n -alkanes (C 21 –C 33 ) were analyzed. Our data show several distinct climate intervals that primarily indicate changes in bog surface moisture. In the early Holocene (c. 9.5–7.7 cal ka BP), wetter conditions are defined by the presence of wetland sedges and grasses, higher concentrations of mid-chain length n -alkanes, and a similarity in δD values among homologs. A dry mid-Holocene (c. 7.7–3.8 cal ka BP) is inferred from the presence of a heath shrubland, low peat accumulations rates, and significant differences between δD values of mid- and long-chain length n -alkanes. The late Holocene (c. 3.8 cal ka BP-present) is marked by the onset of wetter conditions, lateral bog expansion, and an increase in sedges and grasses. The Hollabåttjønnen Bog record is also significant because its margins were an important location for human settlement. We correlate early Holocene environmental conditions with changes in Stone Age structures recently excavated, and we identify the occurrence of coprophilous fungi, such as Sporormiella and Sordaria , likely associated with reindeer grazing activity beginning c. 1 cal ka BP. This site therefore provides important regional paleoclimate information as well as context for evaluating local prehistoric human-environment ...